Fotografi Monokromatik Hitam Putih Dalam Dunia Fotografi Modern - Michel Sutedja; Fairuz Athoriq (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2021)
Abstract — Over the last two decades, photographing in color is a very common thing in the world of photography. Even beginners in the world of photography can be said to have abandoned black and white photos. Most of the oldest people in this modern era know color photography from the first time they know the world of photography itself, in contrast to those who were born in the early days where the world of photography only knows black and white. The visualization of black and white monochoromatic photography is capturing and speaking through colorless photos by relying on the visualization of depth and contrast in strong and clear. Prior to the 20th century, photography without color or black and white was a normal and normal way of recording images, whereas in the modern world like today most people were more familiar with color photography. However, some people still argue that black and white monochoromatic photographs are important for documentation, art, and journalism. Monochromatic black and white photos create a unique impression that cannot be seen in color photos. The comoposition, depth of field and level of contrast in a black and white monochromatic photo can present a different scene from the same photo displayed in a color photo and often do not require further processing with image processing software because they can display their own beauty and uniqueness. The visualization of black and white monochromatic photography is capturing and speaking through photos without the presence of color by relying on the visualization of depth and contrast in strong and clear.Keywords: Photography, Monochromatic , Journalism, Black and White.Abstrak — Lebih dari dua dekade terakhir memotret dalam format berwarna adalah hal yang sangat jamak dalam dunia fotografi. Pemula dalam dunia fotografi pun dapat dikatakan sudah meninggalkan foto hitam putih. Kebanyakan orang tertuama di jaman modern ini mengenal fotografi berwarna sejak pertama kali mengenal dunia fotografi itu sendiri, berbeda dengan mereka yang terlahir pada masa awal dimana dunia fotografi hanya mengenal hitam putih. Visualilsasi dari fotografi monokoromatik hitam putih adalah menangkap dan berbicara melalui foto tanpa warna dengan mengandalkan visualisasi kedalaman dan kontras secara kuat dan jernih. Walaupun demikian, sebagian orang tetap berpendapat bahwa foto monokoromatik hitam putih penting untuk dokumentasi, seni, dan jurnalisme. Foto monokromatik hitam putih menciptakan impresi yang unik dan hal itu tidak dapat dilihat dalam foto berwarna. Komoposisi, kedalaman ruang dan tingkat kekontrasan dalam foto monokromatik hitam putih dapat menampilkan sebuah pemandangan yang berbeda dari foto yang sama yang ditampilkan dalam fotmat berwarna dan sering kali tidak memerlukan pengolahan lebih lanjut dengan perangkat lunak pengolah gambar karena sudah dapat menampilkan keindahan dan keunikannya sendiri. Visualisasi dari fotografi monokromatik hitam putih adalah menangkap dan berbicara melalui foto tanpa kehadiran warna dengan mengandalkan visualisasi kedalaman dan kontras secara kuat dan jernih.Kata Kunci: Fotografi, Monokromatik, Jurnalisme, Hitam Putih